(3ESaGQ GdUHGM GdcGTa Yf eYGfi GdeUHGMs - (3eLghds; (3GdSjO GdTQjas
(3ChdgG (B:s
(3jfJgi TF jSjQkG ef Chdg , hjHOC GdehLhO efg CKfGA GdcdGe Ydi eYfi GdHdGZI Hbhdg (B: (3WQjbI ef GdhVhM hGdNaGA MSHeG jSJOYjg GdebGe , adjS GdeYfi HJeGe GdeQGO s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA (B" (3TQM GdJKdje (B" (3hgh ef ChGNQ GdcJGH ceG XgQ ef agQSI GdcJGH GdeTQhM hgh VhA GdeUHGM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3ai ChdgG JedcGf GdChd SfI (B865(3g`s
(3hGdKGfi (B970(3g` s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs